An Ordinance Concerning the Firing of Guns, & c., Ordinances of the Common Council of the City of Trenton; with the Acts of the Legislature Relative to Said City, at 80, § 1 (1842) - (:unkn) unknown (General Publisher, 1842)
if any person or persons shall fire, discharge, or let off any gun, pistol, squib, or other fire-work within this city, within two hundred yards of any dwelling-house, stable, or any other building, or any hay or grain stack, every such person or persons so offending, and being thereof convicted before any one of the magistrates of this city, either by his own view, by the confession of the offender, or by the oath or affirmation of one credible witness, shall forfeit and pay for every such offence the sum of one dollar,
--
Keywords: DISCHARGE